If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2a + 36 = 4a + -14 Reorder the terms: 36 + 2a = 4a + -14 Reorder the terms: 36 + 2a = -14 + 4a Solving 36 + 2a = -14 + 4a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-4a' to each side of the equation. 36 + 2a + -4a = -14 + 4a + -4a Combine like terms: 2a + -4a = -2a 36 + -2a = -14 + 4a + -4a Combine like terms: 4a + -4a = 0 36 + -2a = -14 + 0 36 + -2a = -14 Add '-36' to each side of the equation. 36 + -36 + -2a = -14 + -36 Combine like terms: 36 + -36 = 0 0 + -2a = -14 + -36 -2a = -14 + -36 Combine like terms: -14 + -36 = -50 -2a = -50 Divide each side by '-2'. a = 25 Simplifying a = 25
| 2.67x+3x=102 | | (x-2)2+(y-4)2=36expand | | 5x+10=-26 | | 34616.0131=B*45.3 | | ln(4x)+1=3 | | (v+39)+5v=11v-36 | | 3679.6530=171.9464*h | | 5k-12=-22 | | -4x-16=-33 | | cbrt(x)+cbrt(x-16)=cbrt(x-8) | | 1378384.64=4534.16*h | | (x-2)2+(y-4)2=36 | | g(p+3)=2x^2+5x+2 | | 9x-5=32 | | 7(x-3)=(4x+5) | | (2k-1)x^2-7x+(k+9)=0 | | 8a-28+3a=9a | | 22(x-5)+1x=-11-(x-1) | | 2a-19=7a+31 | | 6a-5a=13 | | 12p-16=-44+16p | | (p*p*p)-(1p*2p)=(p*p)+40p | | 4x^2=1764(-25x^2) | | 4x^2=1764-25x^2 | | 4x^2=-25x^2 | | 50+60+x+70=180 | | (p*p*p)-(2p*2p)=(p*p)+40p | | 4z+2+4z=10z-22 | | 5(u-8)-5=-3(-8u+9)-3u | | (6z-46)+33=5z+14 | | 3d+4(d-2)= | | x^2=7+2 |